Has globalization triggered collective impact of national intelligence on economic growth? - Nik Ahmad Sufian Burhan@Jaohari; Abdul Halim Sidek; Yohan Kurniawan; Mohd Rosli Mohamad (2015)
Previous studies found that the impact of intelligence (IQ) on productivity is larger at a country level than at an individual level. Labor works in clusters at the country level, and therefore, the effect of individual skill complementarities collectively magnifies per capita income at the national level, which is consistent with the O-ring theory of economic development. The main feature of the O-ring theory is positive assortative matching, in which individuals can augment productivity per capita when they team up with other individuals with equivalent levels of skills. We investigated whether global integration would intensify this impact owing to global interconnectivity of skills and intellectual ideas. By extending the O-ring theory, we examined the role of economic globalization (i.e., actual flows and restrictions), social globalization (i.e., personal contact, information flows, and cultural proximity), and political globalization in moderating the impact of national IQ on the economic growth of more than 110 countries during 1970–2010. The results of our hierarchical multiple regressions suggest that IQ rather than economic, political, or social globalization has the strongest impact on economic growth. Moreover, moderation analysis revealed that globalization has reduced the impact of national IQ on economic growth at the cross-country level. We suggest that within the context of globalization, friction was present in the matching market and cognitive skill-sorting inefficiencies, which reduced the collective impact of IQ on economic growth.